Heme impairs the ball-and-chain inactivation of potassium channels - Sahoo, Nirakar (National Academy of Sciences, 2013)
Fine-tuned regulation of K(+) channel inactivation enables excitable cells to adjust action potential firing. Fast inactivation present in some K(+) channels is mediated by the distal N-terminal structure (ball) occluding the ion permeation pathway. Here we show that Kv1.4 K(+) channels are potently regulated by intracellular free heme; heme binds to the N-terminal inactivation domain and thereby impairs the inactivation process, thus enhancing the K(+) current with an apparent EC(50) value of ∼20 nM. Functional studies on channel mutants and structural investigations on recombinant inactivation ball domain peptides encompassing the first 61 residues of Kv1.4 revealed a heme-responsive binding motif involving Cys13:His16 and a secondary histidine at position 35. Heme binding to the N-terminal inactivation domain induces a conformational constraint that prevents it from reaching its receptor site at the vestibule of the channel pore.